2015
DOI: 10.1177/0271678x15606462
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of prostaglandin E2 receptor EP3 mitigates thrombin-induced brain injury

Abstract: Prostaglandin E 2 EP3 receptor is the only prostaglandin E 2 receptor that couples to multiple G-proteins, but its role in thrombin-induced brain injury is unclear. In the present study, we exposed mouse hippocampal slice cultures to thrombin in vitro and injected mice with intrastriatal thrombin in vivo to investigate the role of EP3 receptor in thrombin-induced brain injury and explore its underlying cellular and molecular mechanisms. In vitro, EP3 receptor inhibition reduced thrombin-induced hippocampal CA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 49 publications
2
64
0
Order By: Relevance
“…An accelerating rotarod was used to measure motor function and balance [36]. The rotarod treadmill (Accuscan, Inc., Columbus, OH, USA) provided a motor balance and coordination assessment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An accelerating rotarod was used to measure motor function and balance [36]. The rotarod treadmill (Accuscan, Inc., Columbus, OH, USA) provided a motor balance and coordination assessment.…”
Section: Methodsmentioning
confidence: 99%
“…Brains were removed and stored in 4% paraformaldehyde overnight and then transferred to 30% sucrose in PBS for another 48 h. Frozen serial coronal brain sections were sliced at 30 μm on a cryostat. Sections were used for Luxol fast blue staining (day 28, n=5/group), Cresyl violet staining (days 3 and 28, n = 8/group), Fluoro-Jade B (FJB) staining (day 3, n=6/group), and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL; day 3, n=6/group) [32, 36]. Mice assigned to propidium iodide (PI) staining (day 3, n=6/group) and hydroethidine analysis (day 3, n=6/group) were perfused with PBS only.…”
Section: Methodsmentioning
confidence: 99%
“…In brief, brain sections were stained with H&E or Cresyl violet solution according to standard procedures [33,44,4850], and then mounted onto microscope slides with Permount (Thermo Fisher Scientific). Staining was visualized under a light microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence staining was performed according to our previously published protocols [44,50]. Briefly, brain sections (6 μm) or cultured cells were incubated with primary antibodies against 8-hydroxyguanosine (8-OHdG, Abcam), Nrf2 (1:100, Abcam), SIRT1 (1:50, Santa Cruz), caspase-3 (1:100, Cell Signaling), and NeuN (1:200, cat# MAB377, EMD Millipore, USA) overnight at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…We and others have shown that EP1 and EP3 receptor signaling has toxic effects in in vitro and in vivo models of ICH 6,7 and in thrombin-induced brain injury. 8 In contrast, EP2 receptor signaling protects cultured neurons under various conditions through the cAMP/PKA or cAMP/Epac pathway [9][10][11][12] and regulates microglial activation and function in vitro. [13][14][15][16] These findings reflect cell-specific differences in EP2 signaling.…”
Section: Introductionmentioning
confidence: 99%